Merkel cell carcinoma: Clinical outcome and prognostic factors in 351 patients. Issue 8 (22nd May 2018) - van Veenendaal, Linde M.; van Akkooi, Alexander C. J.; Verhoef, Cees; Grünhagen, Dirk Jan; Klop, W. Martin C.; Valk, Gerlof D.; Tesselaar, Margot E. T.
Abstract : Background: Merkel cell carcinoma (MCC) is a rare and aggressive neuroendocrine carcinoma of the skin. Aim: To describe clinical outcome and prognostic factors of MCC patients in two expert‐centers. Method: Patients with histologically confirmed MCC in 1990‐2014 were included. Data on patient, tumor characteristics and treatment were retrospectively collected. Results: A total of 351 Patients were evaluated, 153 (44%) males, median age 74 years (range 28‐94). Median follow‐up time was 28 months (IQR 13‐58). Median primary tumor size was 17 mm (range 2‐135). At time of diagnosis 112 (32%) patients had lymph node metastases. The cohorts′ 5‐year overall survival (OS) was 58%. Using a competing risk analysis the 5‐year relapse and MCC related death was 42% and 22%. Adjuvant radiation therapy (XRT) was associated with reduced recurrence (SDH 0.54; CI 0.3‐0.9). Nodal involvement (SDH 2.7; CI 1.1‐6.6) and the male gender were associated with higher MCC related death (SDH 3.1; CI 1.2‐7.9) Conclusion: In a large cohort a low MCC related death, in the presence of a low OS was seen. This indicates that a significant number of MCC patients die due to other causes than MCC. Adjuvant XRT was associated with relapse. Male gender and nodal metastasis were associated with MCC related death.